Sports participation and performance 5 years after arthroscopic partial meniscectomy: A retrospective cohort study of 288 patients - Giladi, J. O.; Holsgaard-Larsen, A.; Varnum, C.; Thorlund, J. B. (Journal of Orthopaedic & Sports Physical Therapy, 2022)
Objective